PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA GOOGLE SITES TERHADAP PENINGKATAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Metha Lolyta Sitanggang; Tita Juwitaningsih (Chemistry Education Practice, 2025)
This research is motivated by the low learning outcomes and activities of students in chemistry material, especially electrolyte and non-electrolyte solutions, which are caused by the dominance of conventional learning methods and the lack of use of innovative digital media. The research was conducted at SMAS Budisatrya in the 2024/2025 academic year. The objectives of this study were (1) to determine the effect of implementing a problem-based learning model assisted by Google Sites media on improving student learning outcomes; (2) to determine the effect of implementing a problem-based learning model assisted by Google Sites media on student learning activities; (3) to determine the relationship between learning activities and student learning outcomes in electrolyte and non-electrolyte solution material. The population in this study was all class X of SMAS Budisatrya. Sampling was carried out using a random sampling technique and the classes used were class X-2 as the experimental class and X-3 as the control class. Hypothesis testing was carried out using a right-sided one-tailed t-test. The results of the study at a significance level of α = 0.05 showed that Sig (2-tailed) <0.05 (0.000 <0.05) then Ha was accepted, there was an increase in student learning outcomes taught with the Problem Based Learning learning model assisted by Google Sites Media on the material of Electrolyte and Non-Electrolyte Solutions. The average increase in student learning outcomes in the experimental class was 77.21% with a high category and the average increase in student learning outcomes in the control class was 50% with a moderate category. The correlation test of learning activities on improving student learning outcomes showed Sig (2-tailed) = 0.002 at a significance level of α = 0.05, then Ha was accepted, there was a correlation between learning activities and improving learning outcomes.